PERAN WORLD HEALTH ORGANIZATION (WHO) DALAM MENANGANI KASUS PERDAGANGAN ORGAN MANUSIA ILEGAL DI CHINA - Ella Windiarti; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to explain the cooperation of state actors in the form of intergovernmental organizations (IGOs) with non-governmental organizations (NGOs). The case study taken is the Role of the World Health Organization (WHO) in Handling Cases of Illegal Organ Trafficking in China, the IGO which is engaged in global public health, raised the issue of organ trafficking in China in 2008, as an international problem that should not be underestimated. This problem has existed for a long time, because the Chinese government legalized organ harvesting from executions. Emerged from various circles, both the Chinese community itself and international organizations engaged in other human rights fields. This case emerged when the data provided by the Chinese government did not synchronize with the investigations by the United Nations, WHO and other international organizations that helped with this problem.This study uses a pluralism perspective which explains that the presence of non-state actors has an important role in the dynamics of international relations. This descriptive qualitative research uses data collection techniques through document analysis or analyzing secondary data, such as books, journals, official publications, reports, and websites to explain how the cooperation exists in dealing with cases of illegal human organ trafficking.The role of the Chinese government is very important in stopping organ trafficking cases in China. Through several actions taken by WHO, the United Nations and international organizations in dealing with cases of organ trafficking in China to achieve the goal, there are several obstacles. The involvement of the Chinese government, the health sector, as well as the entry of the Chinese military made this problem difficult to overcome, so that it became a protracted problem.Keywords: China, NGO, IGO, WHO, Human Rights and Human Organ Trafficking